2023
DOI: 10.1111/sms.14423
|View full text |Cite
|
Sign up to set email alerts
|

Wheelchair rugby players maintain sprint performance but alter propulsion biomechanics after simulated match play

Abstract: The study aimed to explore the influence of a sports‐specific intermittent sprint protocol (ISP) on wheelchair sprint performance and the kinetics and kinematics of sprinting in elite wheelchair rugby (WR) players with and without spinal cord injury (SCI). Fifteen international WR players (age 30.3 ± 5.5 years) performed two 10‐s sprints on a dual roller wheelchair ergometer before and immediately after an ISP consisting of four 16‐min quarters. Physiological measurements (heart rate, blood lactate concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Studies have shown that the same maximal speed can be achieved using different propulsion techniques. The technique parameters that are varied include propulsion cadence, force applied to the handrim, and different propulsion recovery times ( 34 ). This knowledge challenges the notion of performance degradation, since the variance in propulsion technique parameters does not necessarily imply lower performance levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the same maximal speed can be achieved using different propulsion techniques. The technique parameters that are varied include propulsion cadence, force applied to the handrim, and different propulsion recovery times ( 34 ). This knowledge challenges the notion of performance degradation, since the variance in propulsion technique parameters does not necessarily imply lower performance levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this winning paper from the Physiology and Biochemistry Section, the following papers from each of the other sections were also highly commended. In the Biomechanics and Motor Control section, a paper by Briley et al 2 studied wheelchair rugby players using threedimensional thorax and bilateral glenohumeral kinematics following a sports-specific intermittent sprint protocol. The results showed that the wheelchair rugby players were able to maintain sprint performance by altering kinetics, joint kinematics, and asymmetries of wheelchair sprinting.…”
Section: Sjmss Paper Of the Year 2023mentioning
confidence: 99%